The genus Caligus Müller, 1785 (Copepoda: Siphonostomatoida): two new species from reef associated fishes in New Caledonia, and some nomenclatural problems resolved - Hayes, Polly; Justine, Jean-Lou; Boxshall, Geoffrey A. (Zootaxa, 2012)
Caligus praecinctorius sp. nov. is described on the basis of females taken from the gills of Gymnocranius grandoculisValenciennes, 1830, G. euanus (Günther, 1879) and Epinephelus fasciatus (Forsskål, 1775), all caught in New Caledonia.The new species is characterised by having the posteromedian lobe of the cephalothorax completely covering the fourthpedigerous somite in dorsal view, and by the genital complex being 2.7 times wider than long. A second new species, C.macoloricola sp. nov., is described based on material from the gills of Macolor niger (Forsskål, 1775). It is distinguishedby the combination of a 3-segmented leg 4 with 4 spines on the distal segment, a vestigial post-antennal process, and theconfiguration of the setal elements on the exopod of leg 1. The status of a number of other Caligus species is reviewed. Itis proposed to treat C. angustatus Krøyer, 1863 as a junior subjective synonym of C. gurnardi Krøyer, 1863, C. dactylusHo, Lin & Chang, 2007 as a junior subjective synonym of C. dactylopteni Uma Devi & Shyamasundari, 1981, and C.kirtioides Ho & Lin, 2004 as a junior subjective synonym of C. jawahari Hameed & Adamkutty, 1985. Caligus bifurcatusPearse, 1952 is recognised as a junior subjective synonym of Tuxophorus caligodes Wilson, 1908. Caligus cristatusGould, 1841 is here treated as a species inquirendum in the pandarid genus Dinemoura Latreille, 1829. Caligus elevatusKirtisinghe, 1964 is discovered to be an incorrect subsequent spelling of C. clavatus Kirtisinghe, 1964. Caligus gayiNicolet, 1849 is here treated as a species inquirendum. It is proposed to treat C. oligoplitisi Carvalho, 1956, C. validusPearse, 1952 and C. mercatoris Capart, 1941 as junior subjective synonyms of C. robustus Bassett-Smith, 1898 and a listof known hosts of this species is presented. Caligus pterois Kurian, 1949 has priority over Caligus russellii Kurien, 1950,which is here treated as a junior objective synonym, since the two descriptions were based on the same material. We rejectCressey’s (1991) proposal to treat C. tenax Heller, 1865 as a synonym of C. chorinemi Krøyer, 1863 and we retain C. tenaxas a valid species. We propose to treat C. spinosurculus Pearse, 1951 as a junior subjective synonym of C. tenax. Wepropose to treat C. multispinosus Shen, 1957 as a junior subjective synonym of C. stromatei Krøyer, 1863. We note thatCaligus trichiuri Krøyer, 1863 is the oldest available name for the taxon Metacaligus uruguayensis Thomsen, 1949. SoCaligus (Metacaligus) uruguayensis Thomsen, 1949 becomes a junior subjective synonym and the valid name for this taxon is Metacaligus trichiuri (Krøyer, 1863).